Clinical supervision and teacher development - Gall, Meredith D., 1942-; Acheson, Keith A., 1925-; Acheson, Keith A., 1925-. (Hoboken, NJ : John Wiley & Sons, 2011)
'Supervising teachers need a practical, streamlined book that presents the tools to succeed in their careers. Gall offers that resource, providing clear, hands-on steps for supervising teachers and encouraging professional growth. This concise book presents a widely accepted and flexible model of clinical supervision as well as numerous research-based and field-tested strategies. It focuses on new and cutting edge information to reflect the latest research and theory. The concepts and techniques covered will help supervising teachers improve in the classroom.'--
Includes bibliographical references and index.
Keywords: Student teaching; Teachers -- In-service training; School supervision; Observation (Educational method).; Teachers' workshops